2015
DOI: 10.1111/1751-2980.12213
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing radiation exposure in patients with inflammatory bowel disease: Are we overexposing our patients?

Abstract: A high percentage of IBD patients are exposed to high CED. Radiation-free cross-sectional examinations, such as MRI, should be used, especially in young patients, those who have undergone prior surgery and those with severe IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 28 publications
2
21
0
2
Order By: Relevance
“…Similar trends have been found in studies following this meta-analysis. A 2015 retrospective review of 325 IBD patients in Chile, reported 19.5% of patients with CD and 2.4% of patients with UC, to be exposed to CED > 50 mSv [13] . A recent United Kingdom retrospective study of 415 patients with IBD referred from primary care, reported a median total CED of 7.2 mSv in CD patients and 2.8 mSv in UC patients, with 8% of IBD patients overall exposed to CED > 50 mSv.…”
Section: Ibd Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar trends have been found in studies following this meta-analysis. A 2015 retrospective review of 325 IBD patients in Chile, reported 19.5% of patients with CD and 2.4% of patients with UC, to be exposed to CED > 50 mSv [13] . A recent United Kingdom retrospective study of 415 patients with IBD referred from primary care, reported a median total CED of 7.2 mSv in CD patients and 2.8 mSv in UC patients, with 8% of IBD patients overall exposed to CED > 50 mSv.…”
Section: Ibd Patientsmentioning
confidence: 99%
“…Risk factors for high radiation exposure in IBD patients have been widely studied [11][12][13][14][15]17] . In a cohort of 354 adult and paediatric patients with CD, Desmond et al [11] identified that patients diagnosed under the age of 17, patients with upper gastrointestinal (GI) disease, penetrating disease, multiple surgeries, or those that required intravenous steroids or infliximab, were at greater risk of receiving high cumulative radiation exposure.…”
Section: Factors Associated With Increased Radiation Exposure In Ibd mentioning
confidence: 99%
See 1 more Smart Citation
“…However, CT can result in a high amount of cumulative radiation 4. As children can be expected to have a longer life expectancy than older individuals, their potential risk for developing cancer due to radiation exposure from diagnostic imaging is also higher 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective experience on 325 IBD patients from a clinic in Santiago, Chile, reported that CD, longer duration of disease, ileal involvement, stricturing behavior, steroid or biologic agents, and CDrelated hospitalizations and surgery were risk factors. A full 19.5 % of their CD patients were exposed to high levels of radiation, defined as CED [50 mSv [16]. In contrast, a smaller retrospective study of 99 CD patients indicated that initiation of an anti-TNF agent decreased radiation exposure in the subsequent year from a CED from 28.1 to 15.0 mSV, unlike steroid treatment, which did not reduce radiation exposure in the subsequent year [17].…”
mentioning
confidence: 99%